SOCIETAS DIALOGAL: MEMBANGUN KARAKTER KOMUNITER BAGI ORANG MUDA INDONESIA DI TENGAH ARUS GLOBALISASI: Refleksi Filosofis atas Societas Dialogal dalam Perspektif Armada Riyanto - Thomas Kadek Lintang Kurniawan; F.X. Eko Armada Riyanto (Jurnal Reinha, 2023)
This paper focuses on deepening the theme of dialogic society within the framework of building communitarian character in the Indonesian nation's political education. The method used in this writing is the method of literature by using the book Philosophy of Politics and Relationality by Armada Riyanto. The author's argument discusses dialogically in the context of young Indonesians. Today's young people are faced with developments in technology and communication. Various means can be used to interact with each other. However, sometimes young people fall into miscommunication with others. In other words, young people fall into individuality and neglect living together. Living together or community has an important role for the growth and development of the young people themselves. For that, young people need to build their communitarian character within themselves. The writer finds that there are still young people who often spend their time in their own room or space. In addition, the author also sees that the deepening of the theme of dialogue society in young people brings fresh air to their lives and the surrounding community.